Synovial Mesenchymal Stem Cells Derived From the Cotyloid Fossa Synovium Have Higher Self-renewal and Differentiation Potential Than Those From the Paralabral Synovium in the Hip Joint. Issue 12 (October 2018) - Murata, Yoichi; Uchida, Soshi; Utsunomiya, Hajime; Hatakeyama, Akihisa; Nakashima, Hirotaka; Chang, Angela; Sekiya, Ichiro; Sakai, Akinori
Background: Several studies have shown the relationship between poorer clinical outcomes of arthroscopic femoroacetabular impingement syndrome surgery and focal chondral defects or global chondromalacia/osteoarthritis. Although recent studies described good outcomes after the conjunctive application of synovial mesenchymal stem cells (MSCs), none demonstrated the application of synovial MSCs for cartilaginous hip injuries. Purpose: To compare the characteristics of MSCs derived from the paralabral synovium and the cotyloid fossa synovium and determine which is the better source. Study Design: Controlled laboratory study. Methods: Synovium was harvested from 2 locations of the hip—paralabral and cotyloid fossa—from 18 donors. The number of cells, colony-forming units, viability, and differentiation capacities of adipose, bone, and cartilage were collected and compared between groups. In addition, real-time polymerase chain reaction was used to assess the differentiation capacity of adipose, bone, and cartilage tissue from both samples. Results: The number of colonies and yield obtained at passage 0 of synovium from the cotyloid fossa was significantly higher than that of the paralabral synovium ( P < .01). In adipogenesis experiments, the frequency of detecting oil red O–positive colonies was significantly higher in the cotyloid fossa than in the paralabral synovium ( P < .05). In osteogenesis experiments, the frequency of von Kossa and alkaline phosphatase positive colonies was higher in the cotyloid fossa synovium than in the paralabral synovium ( P < .05). In chondrogenic experiments, the chondrogenic pellet culture and the gene expressions of COL2a1 and SOX9 were higher in the cotyloid fossa synovium than in the paralabral synovium ( P < .05). Conclusion: MSCs from the cotyloid fossa synovium have higher proliferation and differentiation potential than do those from the paralabral synovium and are therefore a better source. Clinical Relevance: Synovial cells from the cotyloid fossa synovium of patients with femoroacetabular impingement syndrome are more robust in vitro, suggesting that MSCs from this source may be strongly considered for stem cell therapy.